Eksplorasi Proses Kognitif Anak Usia Dini Dalam Menyelesaikan Pola Berulang - Siti Azkia Salsabiila; Ocih Setiasih (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2024)
Learning repeating patterns is the foundation for children's understanding of other math concepts. However, previous research has shown that there are still children as young as 5-6 years old who have difficulty in finding pattern sequences. The purpose of this study is to identify and discuss the cognitive strategies used by children aged 5-6 years to recognize and solve repeated pattern problems. A qualitative approach with a case study method was used to achieve this goal. The results showed that there were three categories of strategies used by children to solve repetitive pattern problems, namely attention to individual features, comparison and classification, and focus on sequence. For teachers, the results of this study are expected to provide feedback on the learning of repetitive patterns by paying attention to the characteristics and problem solving strategies of each child. For future researchers, this research can be a first reference to further explore the use of the three strategies for solving repetitive patterns in a larger number of 5-6 year old child subjects